PENGEMBANGAN BAHAN AJAR BERBASIS FLIPBOOK PADA MATERI KERAGAMAN BUDAYA DI KELAS IV SEKOLAH DASAR - Yarliza, Defnita; Zahara, Leni; Arwin; Ulya Akmal, Atika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the limited use of digital teaching materials in Natural and Social Sciences (IPAS) learning in elementary schools, where printed textbooks still dominate and student engagement remains low. This research and development (R&D) study aimed to produce flipbook-based teaching materials on Cultural Diversity content for fourth-grade students that are valid, practical, and effective, using the ADDIE model (analysis, design, development, implementation, evaluation). Subjects were fourth-grade students of SDN 27 Paru (trial school), SDN 8 Paru, and SDN 24 Aie Angek (research schools). Data were collected through expert validation sheets, teacher and student practicality questionnaires, and pretest-posttest tests, then analyzed descriptively in percentage form. Results showed validity of 85% for content, 92.5% for media, and 100% for language, all very valid; practicality of 96.87% for teachers and 98.36-98.63% for students, categorized very practical; and effectiveness of 82.10-84.23%, categorized very effective. The developed teaching material is feasible for use in IPAS learning on Cultural Diversity content.